Geomagnetic Field Variations - Glaßmeier, Karl-Heinz (Springer, 2017)
Earth's magnetic field is currently changing dramatically. Is the observed decrease of the dipole moment indicating a future polarity transition? What would be the effects of such a drastic change on system Earth? Can any positive or negative effects on our biosphere or even humans be expected? This book gives a first overview about the geomagnetic field in general and serves as an introduction into geomagnetism. As the topic of the book covers a wide range of scientific disciplines, the first chapter summarises basic principles of geomagnetism and related fields including a historic overview, instruments and measurements, paleomagnetic fields, basics of dynamo theory, etc. The contributed chapters review major results of international activities aiming at understanding the causes and effects of geomagnetic field variations in view of the questions above